INSERTING AREK CULTURE IN A SYLLABUS PROPOSED FOR BIPA CLASS IN INSTITUT TEKNOLOGI SEPULUH NOPEMBER SURABAYA (NOBEL: Journal of Literature and Language Teaching, 2015)
In view of the need of multiculturalism and Indonesian cultures introduction to BIPA learners, the teaching and learning Indonesian cultures develop into essential part beyond the learning of Bahasa Indonesia itself. Countless studies mentioned that learning a foreign language is more meaningful if there is an involvement of the teaching of its culture. In addition to Bahasa Indonesia materials, the materials and references provided for BIPA learners contain rich-cultural Indonesian values, yet – too extensively. In this research, the writers tried to propose a syllabus that supports not only linguistic competence in Bahasa Indonesia but also more local culture values which is close to BIPA learners’ context. The local culture context applied in this research is Surabaya culture, Arek culture. R&D research method was used and the framework of teaching culture by Brooks (1968) was included in this study. The finding of this study provided valuable implications to BIPA learners as well as BIPA instructors with regards to Bahasa Indonesia competences and the introduction of one of local culture values in Indonesia.